Phase-variable Type I methyltransferase M.NgoAV from Neisseria gonorrhoeae FA1090 regulates phasevarion expression and gonococcal phenotype - Adamczyk-Poplawska, Monika; Bacal, Pawel; Mrozek, Agnieszka; Matczynska, Natalia; Piekarowicz, Andrzej; Kwiatek, Agnieszka (Frontiers in Microbiology, 2022)
Composed of methyltransferase (MTase) and restriction endonuclease, the restriction-modification (RM) systems are compared to a primitive, innate, prokaryotic immune system, controlling the invasion by foreign DNA. The biological significance of RM systems extends beyond their defensive function, but the data on the regulatory role of Type I MTases are limited. We have previously characterized molecularly a non-canonical Type I RM system, NgoAV, with phase-variable specificity, encoded by Neisseria gonorrhoeae FA1090. In the current work, we have investigated the impact of M.NgoAV (methyltransferase NgoAV) activity on gonococcal phenotype and on epigenetic control of gene expression. For this purpose, we have constructed and studied genetic variants (concerning activity and specificity) within M.NgoAV locus. Deletion of M.NgoAV or switch of its specificity had an impact on phenotype of N. gonorrhoeae. Biofilm formation and planktonic growth, the resistance to antibiotics, that target bacterial peptidoglycan or other antimicrobials, and invasion of human epithelial host cells were affected. The expression of genes was deregulated in gonococcal cells with knocked-out M.NgoAV gene and the variant with new specificity. For the first time, the existence of a phasevarion (phase-variable regulon), directed by phase-variable Type I MTase, is demonstrated.